Correction to: Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime (Nature Communications, (2024), 15, 1, (2002), 10.1038/s41467-024-46145-7) - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-46145-7, published online 05 March 2024 In this article, Junsheng Luo and Bowen Liu should have been denoted as equally contributing authors. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17